Activating Community-Based Change Pathways for Stunting Prevention: Integrating Appropriate Technology and Primary Health Cadre Capacity in Rural Indonesia - Tri Sunarsih; Kharisma Kharisma; Ari Okta Viyani; Suyitno Suyitno; Murry Harmawan Saputra; Jeki M.W. Wibawanti; Endah Puji Astuti; Elvika Fit Ari Shanti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Stunting continues to affect many children in rural areas of Indonesia. In these settings, households often face limited food access, constrained health services, and economic hardship. Programs that focus only on nutrition-specific interventions rarely address these broader conditions. Community-based approaches that combine appropriate technology, household food production, and strengthened roles of local health volunteers remain underexplored, particularly in village contexts. Objective: This research examined changes in community knowledge, practical skills, and everyday practices after Women Farmer Groups (Kelompok Wanita Tani – KWT) and posyandu cadres received training in appropriate technology and nutrition education in Srikayangan Village, Kulon Progo. Methods: A convergent mixed-methods approach was applied. The quantitative component used a quasi-experimental single-group pretest–posttest design involving 30 KWT members and 78 cadres. The qualitative component drew on field observations, focus group discussions, interviews, and documentation of program activities. Quantitative results were summarized descriptively and compared across time points, while qualitative materials were interpreted through thematic analysis and then considered together with the quantitative patterns. Anthropometric indicators such as HAZ/LAZ were not included; the evaluation centered on capacity building and shifts in community practice. Results: Scores for knowledge rose markedly, with increases ranging from 40% to 86%. KWT participants also became more confident in using simple food-processing technologies, while cadres showed improvements in several aspects of nutrition service delivery. Field notes and interviews pointed to practical changes at the community level: greater use of locally available foods, growing interest in small-scale food enterprises, and more consistent child growth monitoring activities. Because the design did not include a comparison group, these patterns should be interpreted as observed improvements over time rather than direct causal effects. Conclusion: Combining appropriate technology training with nutrition education appeared to strengthen several intermediate factors linked to child nutrition within households and the community. The study did not measure stunting prevalence, yet the approach offers a promising community model that may be adapted elsewhere. Further research is needed to examine longer-term outcomes.